Nachhaltiger Gebirgs- und Wüstentourismus in Südmarokko? - Popp, Herbert (ERDKUNDE, 2004)
The term sustainability is used today in different disciplines and subjects. This is also true for tourism research. Starting with a critical discussion and reflection of this key term the article wants to give empirical evidence concerning the question of how far trekking and desert tourism in Southern Morocco can be called sustainable, as regards the dimensions of economic, socio-cultural and ecological sustainability. The result is that in general both forms of tourism can indeed be classified as sustainable. Answering the question if this estimation has to be seen in relation with the early stage of both in the respective touristic life cycle the following arguments are developed: (a) trekking tourism will probably continue to be sustainable; (b) desert tourism shows an invasion of external capital and is threatened by future resource bottlenecks and land use conflicts - a tendency which may result in the fact that desert tourism in Morocco could leave the path of sustainability.